Higher-order Hahn's quantum variational calculus - Cruz, Artur M. C. Brito da (2012)
We prove a necessary optimality condition of Euler-Lagrange type for quantum variational problems involving Hahn's derivatives of higher-order. (C) 2011 Elsevier Ltd. All rights reserved.